Recognition of tumor cells by Dectin-1 orchestrates innate immune cells for anti-tumor responses - Shiho Chiba; Hiroaki Ikushima; Hiroshi Ueki; Hideyuki Yanai; Yoshitaka Kimura; Sho Hangai; Junko Nishio; Hideo Negishi; Tomohiko Tamura; Shinobu Saijo; Yoichiro Iwakura; Tadatsugu Taniguchi (eLife, 2014)
The eradication of tumor cells requires communication to and signaling by cells of the immune system. Natural killer (NK) cells are essential tumor-killing effector cells of the innate immune system; however, little is known about whether or how other immune cells recognize tumor cells to assist NK cells. Here, we show that the innate immune receptor Dectin-1 expressed on dendritic cells and macrophages is critical to NK-mediated killing of tumor cells that express N-glycan structures at high levels. Receptor recognition of these tumor cells causes the activation of the IRF5 transcription factor and downstream gene induction for the full-blown tumoricidal activity of NK cells. Consistent with this, we show exacerbated in vivo tumor growth in mice genetically deficient in either Dectin-1 or IRF5. The critical contribution of Dectin-1 in the recognition of and signaling by tumor cells may offer new insight into the anti-tumor immune system with therapeutic implications.